Food vendor stories on food system and livelihood - Prain, Gordon; Bertuso, Arma; Ricarte, Phoebe (CGIAR System Organization, 2024)
This video, showed during the Urban Food System Policy Forum organized by the CGIAR Resilient Cities Initiatives and Quezon City Government held last November 6, 2024, highlights the crucial role of market vendors in urban food systems in the city. Two market vendors spoke candidly about their involvement in the food supply chain and the crucial role that food vending plays in sustaining their households. Their testimonies illustrated the challenges they face—ranging from financial instability to the lack of access to formal business training. But they also emphasized the deep sense of purpose they feel in providing affordable food to their communities.